Effects of brucea javanica seed extract on fetal implantation and estrogen and progesterone levels in female ICR mice / Wardah Ismail - Ismail, Wardah (2015)
Brucea javanica (Buah Makassar) a common herbicious plants in Asia, are widely used in traditional medicine for treating some. However, there is lack of reports with regards to its usage in treating reproductive functions. There is possibility that this herb may affect some reproductive functions. This research was therefore endeavored to determine the possible effects of Brucea javanica extracted from the seeds on mice implantation function. Concurrently, a hormonal study was also done to determine the level of both gonadal hormones important for reproductive functions, estrogen and progesterone during pregnancy with the treatment with the seed extracts. Thirty-two pregnant female ICR mice were divided into four groups of eight each. Group A was given distilled water as control while groups B, C, and D were given oral daily doses of 500, 800, and 1000 mg/kg body weights of Brucea javanica seed extract respectively. Treatment were done for fourteen days. Observations were made as to determine the physical effects of the treatment. Laparotomy was done at day seventeen of the pregnancy to determine number of fetal implantations. Blood samples were collected determination of the hormones. Results obtained showed no significant changes to the number of fetal implantation to all groups. Similarly, there was no significant change in hormonal levels and no obvious change in the physical attributes of the mice. These findings suggest that Brucea javanica seed extract have no effect in implanted fetuses and seem to be safe to be taken during pregnancy.